Worship in the network culture liturgical ritual studies; fields and methods, concepts and metaphors - Barnard, Marcel 1957-; Cilliers, Johan 1954-; Wepener, Cas 1972- (Leuven [u.a.] Peeters, 2014)
Literaturverz. S. [391] - 415
Worship signifies a wide field of liturgical ritual practices that extend from the Sunday morning service in a mainline church through a worship service in an African Independent Church to Christian ritual on the internet and cultural ritual-symbolic practices. Solid and solidified concepts are no longer sufficient for the study of this liquid field. This book approaches liturgical ritual from a different perspective. The first part of this book maps and explores the field of liturgical ritual studies. The second part of the book takes a first step in the process of conceptualisation and elaborates on the sensitising concept of liminality. In part three various aspects of the field are elaborated on in six double perspectives: bricolage/particularity, language/silence, image/sound, embodiment/performance, play/function, time/space. Part four reviews the road that the book has covered to this point from the two theological perspectives that characterise Protestant worship: Sacrament/Word and Prayer/Worship
Introduction: Worship in the network cultureI. Fields and methods : mapping and exploring the field -- Worship and liturgical ritual : sketches -- Worship as liturgical ritual -- Investigating liturgical ritual -- II. Liminality : a sensitising concept and metaphor -- Connected/rooted : anthropological perspectives on liminality -- Descended/ascended : theological perspectives on liminality -- III. Concepts and metaphors -- Bricolage/particularity -- Language/silence -- Image/sound -- Embodiment/performance -- Play/function -- Time/space -- IV. Theological review -- Sacrament/word -- Worship/prayer -- Epilogue: Liminality reviewed.
Literaturverz. S. [391] - 415
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Liturgics